PENGARUH PEMBERIAN PUPUK ORGANIK CAIR (POC) NASA TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN JAGUNG - Lakoro, Jefri; Djamaluddin, Ismail (Jurnal Ilmiah Mahasiswa Fakultas Pertanian, 2023)
This research was conducted from August to November 2020. On farmland in East Longkoga Village, Subdistrict. Bualemo, Banggai Regency. This study aims to determine the effect of NASA POC on the growth and production of corn plants.  Using a Group Randomized Design (RAK) consisting of five treatments and controls. The observation parameters of this study include plant height (cm), number of leaves (strands), cob length (cm), and cob weight (kg). The results of the analysis showed that NASA's POC application of the growth and production of sweet corn plants (Zea mays L) had a very real effect on corn plant height at 3,4,6 and 8 MST, real on the number of leaves at 8 MST and not real on the length and weight of the cob. The treatment using NASA POC is with an average plant height of 3, 4, 6 and 8 MST respectively P4, P1, P4 and P3 treatments the average number of leaves at 8 MST namely P3 and P4 treatment, the average length of the cob is P1 and P4 treatment, and the average weight of the cob is P4 treatment.